Has the fed reacted asymmetrically to stock prices? - Søren Hove Ravn (Danmarks Nationalbank, 2011)
Yes. Existing studies of the possible role of asset prices in monetary policy implicitly assume that central banks respond to asset price movements in a fully symmetric way. This paper offers a new perspective by allowing for different policy reactions to stock price increases and decreases, respectively. To avoid endogeneity problems, I employ the method of identification through heteroskedasticity. I then demonstrate that the reaction of the Federal Reserve has indeed been asymmetric during the period 1998- 2008. While a 5% drop in the S&P 500 index is shown to increase the probability of a 25 basis point interest rate cut by 1/3, no significant reaction to stock price increases can be identified.
Keywords: E44; E52; E58; 330; Monetary Policy; Asset Prices; Asymmetries; Geldpolitik; Börsenkurs; Zentralbank; USA